Application of physician-modified fenestrated stent graft in urgent endovascular repair of abdominal aortic aneurysm with hostile neck anatomy: Case report. Issue 46 (November 2016) - Zeng, Rong; Ye, Wei; Liu, Changwei; Wang, Xuan; Song, Xiaojun; Ni, Leng; Liu, Bao; Li, Yongjun; Zheng, Yuehong
Abstract: Background: This study aimed to evaluate the feasibility and effectiveness of the Gore Excluder aortic stent graft (WL Gore & Associates, Inc., Flagstaff, AZ) using the C3 Delivery System after physician modification of fenestration for the urgent treatment of patients with abdominal aortic aneurysm showing hostile neck anatomy. Case summary: Three urgent cases of abdominal aortic aneurysm with hostile neck anatomy symptom with abdominal pain were reported. The same fenestration method was applied to align the target superior mesenteric artery and bilateral renal arteries with 1 scallop and 2 fenestrations, followed by the reconstruction of the target artery using a bare-metal stent or stent graft. Balloon-assisted positioning and image fusion technology were intraoperatively applied to assist the accurate release of the stent graft body. The follow-up periods for all cases exceeded 6 months, showing smooth circulation in the target arteries with no endoleaks. Conclusion: In the absence of other available treatment methods, it is feasible to use a stent graft with physician-modified fenestration for the urgent endovascular repair of abdominal aortic aneurysm with hostile neck anatomy. However, this procedure's long-term efficacy needs to be further investigated.